A multi-institutional and case-matched control study on treatment outcomes of consolidative radiotherapy after a full course of R-CHOP compared with R-CHOP alone in Stage I–II diffuse large B-cell lymphoma (KROG 17-02) - Chung, Mi Joo (J Radiat Res, 2019)
We compared treatment outcomes between rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) chemotherapy alone with R-CHOP followed by consolidative radiation therapy (RT) in diffuse large B-cell lymphoma (DLBCL). We analyzed 404 patients with Stage I–II DLBCL who received six to eight cycles of R-CHOP and achieved a good response after a full course of chemotherapy. Propensity-score matching was used to assess the role of consolidative RT. The R-CHOP alone group (n = 184) was matched in a 1:2 ratio with the R-CHOP plus RT group (n = 92). Twenty-four (13.0%) of 184 patients receiving R-CHOP alone and 8 (8.7%) of 92 patients receiving R-CHOP plus RT had bulky diseases (>7.5 cm). A Deauville score of 1–2 was achieved for 159 (86.4%) of 184 patients receiving R-CHOP alone and 84 (91.3%) of 92 patients receiving R-CHOP plus RT. After a median follow-up time of 42 months, the recurrence-free survival (RFS) rate (86.7% vs 93.0%, P = 0.464) and overall survival rate (88.3% vs 95.1%, P = 0.295) at 5 years did not differ significantly between the R-CHOP alone and R-CHOP plus RT arms. In the additional multivariate analyses, large tumor size (>7.5 cm) was significantly associated with decreased RFS (hazard ratio, 2.368 and confidence interval, 1.837–6.697; P = 0.048). Consolidative radiation was not a significant factor for RFS (P = 0.563). Tumor size was a significant factor for RFS in the rituximab era. The outcome of omitting consolidative RT for good responders after six to eight cycles of R-CHOP chemotherapy was acceptable in early-stage DLBCL without a bulky disease.